Metode 5S Sebagai Upaya Menjaga Keselamatan Kerja dan Kualitas Produk di PT. TS - Ardian rahmaditian; Tarsidi,Yudi prastyo (Journal of Engineering and Applied Technology, 2025)
This study aims to analyze the implementation of the 5S method as an effort to improve occupational safety and maintain product quality at PT. TS. A qualitative descriptive approach was applied through direct observation, interviews, and evaluation using a 5S checklist to assess changes before and after implementation. The results indicate that the application of Seiri, Seiton, Seiso, Seiketsu, and Shitsuke significantly improved workplace organization, cleanliness, and operational discipline. These improvements contributed to reduced safety risks, more efficient work processes, and better control of product quality. Behavioral analysis revealed a positive shift in employee attitudes, reflected in increased awareness, discipline, and initiative in maintaining the work environment. Furthermore, the evaluation of effectiveness showed that consistent standardization and management support played a crucial role in sustaining the implementation of 5S. Overall, the study confirms that the 5S method is not merely a housekeeping tool but a strategic foundation for developing a safe, efficient, and quality-oriented work culture in manufacturing industries